COVID-19, social media, algorithms and the rise of indigenous movements in Southern Africa: perspectives from activists, audiences and policymakers - Foyet, Metolo; Child, Brian (Frontiers in Sociology, 2024)
IntroductionThe COVID-19 pandemic, as a holistic event of cultural trauma, significantly influenced social structures and behaviors globally. Under its impact, social movements leveraged digital platforms to sustain and amplify their causes, creating new forms of solidarity and resistance, and fostering a rise in digital and hybrid collective actions. Concurrently, social media thrived as a transformative tool for social change, revolutionizing communication, mobilization, and advocacy. Platforms like WhatsApp and X redefined traditional activism by enabling rapid information dissemination and facilitating global grassroots movements. This technological evolution has provided marginalized communities, including the indigenous peoples of Southern Africa, with a powerful voice. These communities face challenges such as land rights disputes, environmental degradation, and socioeconomic marginalization. Social media allows them to raise awareness, galvanize support, and engage with a broader audience beyond their geographical confines. The paper hypothesizes that social media plays a multifaceted role in supporting indigenous movements, by not only providing a platform for activists to organize and advocate, but also enabling engagement with the general public and influencing the perspectives and actions of policymakers and other audiences. Through the lenses of rural or indigenous activists who leverage these digital platforms to drive change, audiences who consume and interact with digital content and feeds, and policymakers who are increasingly mindful of the power of social media narratives, this paper aims to understand the complex interplay of forces that shape the trajectory of digital indigenism (indigenous digital activism).MethodsThe paper employs a mixed-methods approach to investigate the influence of social media on social movements among indigenous communities in Southern Africa. The methodology incorporates (a) netnography and in-depth interviews to explore the experiences and strategies of indigenous activists, (b) the counterpublics framework to understand the formation and dynamics of indigenous digital activism, and (c) the Technology-Media-Movements Complex (TMMC) as a theoretical anchor to analyze the interplay between technology, media, and social movements. The case study of the Community Leaders Network (CLN) of Southern Africa is used to contextualize the findings.ResultsFindings reveal that indigenous activists recognize the power of social media in amplifying their voices but use these platforms out of necessity rather than preference. They find social media solutions often misaligned with their contextual needs, citing concerns over platform constraints, privacy issues, cultural insensitivity, superficial engagement metrics, and breaches of consent. Additionally, they reckon that the global emphasis on social media engagement can divert focus from essential field activities that directly benefit local communities, causing social media fatigue. It was also revealed that trying to convey practical information to an audience with preconceived notions is incredibly time-consuming and often feels like an endless loop for indigenous activists. Subsequently, they expressed a desire for platforms that consider users’ mental well-being in their architectural design and incorporate cultural and linguistic practices, suggesting a preference for digital environments that are more aligned with values and modes of communication that contrast with western models.DiscussionThe results underscore social media’s complex role in indigenous movements, highlighting its empowering potential while also presenting significant challenges due to algorithms and platform dynamics. While the ability to share stories, disseminate information about rights abuses, and mobilize support has significantly transformed social movement dynamics in rural communities, social media’s potential for advocacy and mobilization is tempered by challenges that can limit their effectiveness. The findings highlight a pressing need for social media innovations that resonate with indigenous cultural identities, ensuring that their narratives are disseminated in a manner that faithfully preserves their authenticity. The paper discusses the implications of these findings for policymakers, activists, audiences and technology developers, emphasizing the importance of creating digital spaces that are culturally sensitive and supportive of indigenous activism.